TINJAUAN RISET MAHASISWA PROGRAM STUDI MAGISTER MANAJEMEN PENDIDIKAN ISLAM PASCASARJANA UIN ALAUDDIN MAKASSAR (Analisis Kecenderungan dan Bidang Kajian Penelitian Mahasiswa) - Siti Syamsudduha; Ayu Ruqayyah Yunus; Danial Rahman (Universitas Islam Negeri Alauddin Makassar, 2020)
This article aims to describe: (1) Student research trends in terms of themes, fields of study, and methodology; (2) Suitability between research and the student's field of science; and (3) The basis for determining the field of research of students of the Master of Islamic Education Management Study Program at UIN Alauddin Makassar. This research is quantitative descriptive. The samples were determined based on the purposive sampling technique, namely students who had completed their studies were 85 people. The data techniques used were documentation and interviews. Then the results were analyzed through descriptive statistics and supported by interview results. The results showed that: (1) Student research trends, including: (a) tended to be on the theme of schools, madrasah and boarding school; (b) tends to organizational behavior, SBM, and leadership; (c) tends to use a qualitative approach; (2) Students have adjusted their research studies to the field of educational management; and (3) The basis for determining the student's field of study is motivated by its suitability with the field of work, experience in lectures and the work environment, as well as that of a general nature.